Some weak limit laws for the diameter of random point sets in bounded regions - Lao, Wei (KIT Scientific Publishing, 2010)
This book establishes several weak limit laws for problems in geometric extreme value theory. We find the limit law of the maximum Euclidean distance of i.i.d. points, as the number of points tends to infinity, under certain assumptions on the underlying distribution. One of the methods is also applicable for some other functionals, such as the maximum area or the maximum perimeter of triangles formed by point triplets.